Gambaran Penggunaan Tanaman Obat Di Desa Daya Murni Kecamatan Tumijajar Kabupaten Tulang Bawang Barat Tahun 2024 - Mulatasih, Endah; Wulan Syafira, Melsya; Isnenia, Isnenia; Yulyuswarni, Yulyuswarni (JURNAL FARMASI GALENIKA, 2024)
Medicinal plants have long been used by Indonesian people as an alternative traditional treatment. Plants have been an important source of medicine for thousands of years. The use of plants for healing is the oldest form of medicine in the world. The medicinal plants chosen are usually plants that can be used for first aid or light medicines such as coughs and fever. Based on a pre-research survey in Dayamurni Village, it was found that many people still use medicinal plants for various health complaints. This study aims to determine the overview of medicinal plant usage in Dayamurni Village, Tumijajar District, West Tulang Bawang Regency in 2024. This research is a quantitative descriptive study with a quota sampling technique of 100 respondents who meet the inclusion and exclusion criteria. Data collection was carried out through interviews using questionnaires. The results showed that the majority of medicinal plant users were women (83%), aged 40-44 years (19%), with high school education (55%). The most widely used type of plant was ginger (27,0%), with the method of use being drunk (92,9%), in fresh form (92,9%). Usage was generally only when sick (88%), aimed at curing diseases (65%), especially for treating coughs (23,0%). The main source of information was parents (67%), and most did not use accompanying medications (60%).